A new measure of foreign rule based on genetic distance - Dharmapala, Dhammika (CESifo, Center for Economic Studies & Ifo Institute, 2020)
The consequences for countries of past foreign rule are the subject of a vast literature across history and the social sciences. This paper constructs a novel measure of past foreign (or minority) rule - the genetic distance of a country's ruling elite in the year 1900 from the country's ethnic majority - by mapping historical information on these groups to existing data on bilateral genetic distances between countries and populations. This generates an
10419/216598
Keywords: Graue Literatur; foreign rule; fiscal capacity; economic development